Axial obliquity control on the greenhouse carbon budget through middle‐ to high‐latitude reservoirs. (25th February 2015) - Laurin, Jiří; Meyers, Stephen R.; Uličný, David; Jarvis, Ian; Sageman, Bradley B.
Abstract: Carbon sources and sinks are key components of the climate feedback system, yet their response to external forcing remains poorly constrained, particularly for past greenhouse climates. Carbon‐isotope data indicate systematic, million‐year‐scale transfers of carbon between surface reservoirs during and immediately after the Late Cretaceous thermal maximum (peaking in the Cenomanian‐Turonian, circa 97–91 million years, Myr, ago). Here we calibrate Albian to Campanian (108–72 Myr ago) high‐resolution carbon isotope records with a refined chronology and demonstrate how net transfers between reservoirs are plausibly controlled by 1 Myr changes in the amplitude of axial obliquity. The amplitude‐modulating terms are absent from the frequency domain representation of insolation series and require a nonlinear, cumulative mechanism to become expressed in power spectra of isotope time series. Mass balance modeling suggests that the residence time of carbon in the ocean‐atmosphere system is—by itself—insufficient to explain the Myr‐scale variability. It is proposed that the astronomical control was imparted by a transient storage of organic matter or methane in quasi‐stable reservoirs (wetlands, soils, marginal zones of marine euxinic strata, and potentially permafrost) that responded nonlinearly to obliquity‐driven changes in high‐latitude insolation and/or meridional insolation gradients. While these reservoirs are probably underrepresented in the geological record due to their quasi‐stable character, they might have provided an important control on the dynamics and stability of the greenhouse climate. Key Points: Amplitude modulation of axial obliquity controls the Late Cretaceous δ 13 C Transfer of the astronomical signal is examined with mass balance models Quasi‐stable carbon reservoirs at middle to high latitudes provide the link